Analisis Strategis Tekanan Profitabilitas pada Layanan GoFood di Indonesia - Berman J Hutabarat; Kesiayohana Kesiayohana; Krisna Rahmat; Ovalia Rukmana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The online food delivery (OFD) industry in Indonesia is experiencing increasing profitability pressure driven by intense competition, low consumer switching costs, and rising incentive and logistics expenses. These conditions require platforms to shift their strategic focus from aggressive expansion toward sustainable profitability. This study aims to examine GoFood’s strategic position in responding to such pressures and to formulate relevant strategic directions in a maturing market. A case study approach based on desk research was employed, utilizing secondary data analyzed through the PESTEL framework, Porter’s Five Forces, and the VRIO model, which were subsequently synthesized using a SWOT/TOWS matrix. The findings indicate that the OFD industry is characterized by high competitive rivalry and strong buyer power, causing promotion-heavy strategies to exert downward pressure on margins. Internally, GoFood benefits from ecosystem scale, multi-sided orchestration capabilities, data-driven technology, and strong brand equity, while still facing challenges related to service quality variability. The study highlights that service reliability differentiation and the expansion of non-incentive monetization, such as advertising and merchant solutions, are critical strategies for balancing growth and profitability. Academically, this research contributes to the literature on digital platform strategy by providing empirical insights from the OFD sector in an emerging market context.